A Comprehensive Study On Biogas Production (International Journal of Food and Nutritional Sciences, 2022)
Biogas is produced by turning various types of biological waste into gas. It's a sustainable, environmentally friendly fuel made completely from locally sourced biofuels that might utilized in a number of ways, including road vehicle fuel and industrial applications. The organic fertilizers gathered all through the production process contribute to the methane era's circular economic impact. This paper discusses the Biogas technologies and environment efficiency, Health, safety and risk assessment and advantages of biogas production. Biogas may be created from a variety of materials. The greatest essential role in the biogas production procedure is played by microorganisms that graze on waste. Biogas production is an environmentally benign method of generating electricity from biomass, and the waste may be utilized as a soil conditioner. The anaerobic biological decomposition of organic materials produces biogas. Methane and carbon dioxide make up the majority of it.